GE_GERICHTE C/21189/2013 vom 24. Juni 2016 - GE Cour de justice (2016)
DROIT DE VOISINAGE ; INTERDICTION DES IMMISSIONS EXCESSIVES ; ARBRE ; CHOSE JUGÉE | CPC.316.3; CPC.59.2.e; CC.679; CC.684; CC.688;